Determination of organophosphates and organochlorines in forages and bovine milk produced in Pereira-Risaralda (Colombia) - Rodriguez, Jose Alexander (2023)
The aim of this work was to determine the presence of organophosphate (OF) and organochlorine (OC) pesticides in forage and milk from dairy farms in the municipality of Pereira (Colombia). The measurement was carried out by means of gas chromatography coupled with tandem mass spectrometry with subsequent confirmation with gas chromatography with electron micro-capture detector. The results indicate the presence of OF and OC in forage and milk at levels higher than those allowed by the Codex Alimentarius and a presence in 90% of the farms, which were exposed to its application days prior to the measurements, especially of OF. The appearance of OC in is related to its persistence in soil, water, in supplements offered to livestock or their application in the area. Pesticides found in forages were not eliminated in the milk of animals that consumed them at levels that were detectable in this study.